1990
DOI: 10.1123/jsep.12.2.157
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Imagery Rehearsal, Relaxation, and Self-Talk Package on Basketball Game Performance

Abstract: This study investigated the effects of an imagery rehearsal, relaxation, and self-talk package on the performance of a specific defensive basketball skill during competition. Subjects were four female intercollegiate basketball players. A single-subject multiple-baseline-across-individuals design was employed to evaluate the intervention package. The intervention was clearly effective in enhancing a basketball skill during games, and social validity measures were very positive. The need for further research in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 16 publications
1
48
0
4
Order By: Relevance
“…In an arm wrestling study (Nelson & Furst, 1972), the weaker subjects won 10 of 12 matches when both contestants incorrectly believed the weaker person to be stronger than his opponent; when the contestants correctly identified the weaker contestant, the stronger subjects won all 12 matches. Other studies have shown that positive self-talk improves the performance of basketball players (Kendall, Hrycaiko, Martin, & Kendall, 1990), skiers (Rushall, Hall, Roux, Sasseville, & Rushall, 1988), and swimmers (Rushall & Shewchuk, 1989). It is plausible that the positive reinforcement provided by an athlete's success increases self-efficacy and, thereby, enhances performance.…”
Section: Ringer Percentages By Gamementioning
confidence: 99%
“…In an arm wrestling study (Nelson & Furst, 1972), the weaker subjects won 10 of 12 matches when both contestants incorrectly believed the weaker person to be stronger than his opponent; when the contestants correctly identified the weaker contestant, the stronger subjects won all 12 matches. Other studies have shown that positive self-talk improves the performance of basketball players (Kendall, Hrycaiko, Martin, & Kendall, 1990), skiers (Rushall, Hall, Roux, Sasseville, & Rushall, 1988), and swimmers (Rushall & Shewchuk, 1989). It is plausible that the positive reinforcement provided by an athlete's success increases self-efficacy and, thereby, enhances performance.…”
Section: Ringer Percentages By Gamementioning
confidence: 99%
“…These real life competitive athletic situations interest coaches and athletes the most (Kendall et al, 1990) Palmer;1992 …”
Section: Self-talk a Behavioral Analysismentioning
confidence: 99%
“…No entanto, os resultados dos estudos nem sempre têm possibilitado conclusões consistentes, existindo autores que colocam algumas dúvidas quanto à eficácia das estratégias utilizadas e às dimensões da VM a utilizar (ver Lamirand & Rainey, 1994;Savoy & Beitel, 1996;Templin & Vernacchia, 1995), enquanto outros têm vindo a afirmar o peso do treino mental (e da VM) na melhoria das capacidades motoras dos atletas e do rendimento desportivo (ver Kendall et al, 1990;Shambrook & Bull, 1996;Suedfeld & Bruno, 1990;Wollman, 1986). O presente estudo procura ajudar a esclarecer o primeiro tipo de discrepâncias, observando a possibilidade dos atletas incorporarem nas suas rotinas mentais a VM e quais os domínios que poderão beneficiar particularmente com o treino desta competência psicológica.…”
Section: Discussionunclassified